Conceptualising the small-scale public sphere - Stiegler, Zack (Javnost (Ljubljana), 2009)
Community media presuppose not only the existence of larger, dominant media systems, but of multiple smaller, local publics as well. Small-scale public spheres are distinct from the larger public spheres of media not only in size and scope, but also in their character and function. Smallscale public spheres are distinct from the larger public spheres of media not only in size and scope, but also in their character and function. The article explores the work of Nicholas Garnham, Charles H. Cooley and Benjamin Barber as a way to answer the questions of what does such a small-scale public sphere look like, and how might broadcasting operate within it? Media systems based in a small-scale public sphere provide greater opportunities for participation and access than do mass media, but the benefits of community media do not come easily. Three main limitations present barriers to media of the smallscale public sphere: capital investment, restricted access, and apathy.
Keywords: javna sfera; radio; javnost; manjšine; mass media; množični mediji; množično komuniciranje; television; televizija